2017
DOI: 10.1021/acsomega.7b01334
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multiligand Binding Specificity of Saposin B Reveals Two Binding Sites

Abstract: Saposin B (SapB) is a human lysosomal protein, critical for the degradation of O-sulfogalactosylceramide (sulfatide). SapB binds sulfatide and presents it to the active site of the enzyme arylsulfatase A. Deficiency of SapB leads to fatal activator-deficient metachromatic leukodystrophy. Given the conformational flexibility and the large hydrophobic “pocket” produced upon (physiologically relevant) homodimerization, SapB may have broader substrate diversity than originally thought. Herein, we present evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Our simulations indicate that an open SapB dimer binds at least two Gb3-NBD molecules. Furthermore, these results are consistent with reports describing in vitro experiments showing SapB dimers binding two phospholipids 50 and in silico experiments showing SapB dimers binding two small molecules 51 .…”
Section: Discussionsupporting
confidence: 92%
“…Our simulations indicate that an open SapB dimer binds at least two Gb3-NBD molecules. Furthermore, these results are consistent with reports describing in vitro experiments showing SapB dimers binding two phospholipids 50 and in silico experiments showing SapB dimers binding two small molecules 51 .…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, no specific small-molecule inhibitor has been developed for this purpose. However, from literature, we found that the antimalarial drug hydroxychloroquine binds to saposin B (47). Hydroxychloroquine is an immunomodulating drug used to treat rheumatoid arthritis and systemic lupus erythematosus (SLE), and recent studies showed antiatherosclerotic effects in patients with SLE (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggest that the binding of one molecule of CoQ 10 may accelerate the binding of two molecules of α-tocopherol. The crystal structure of saposin B binding chloroquine was later resolved [153] and molecular docking studies identified two binding sites that are accessible to a variety of ligands [154].…”
Section: Saposin B Binds Coq 10 and Regulates Coq 10 Contentmentioning
confidence: 99%